Non-contact neuromodulation of the human autonomic nervous system function via different odors: Sex, menstrual cycle, and odor dose- and duration-specific effects - Maharjan, Ashim; Khwaounjoo, Prashanna; Peng, Mei; Cakmak, Yusuf Ozgur (Frontiers in Neuroscience, 2022)
In recent decades, it has been uncovered that the autonomic nervous system (ANS) can be influenced using non-contact neuromodulation via odor stimulation. Increasing parasympathetic-vagal activation of the ANS is integral to improving the sympathovagal balance between the sympathetic- and parasympathetic nervous systems, which is often imbalanced in several chronic inflammatory disorders, such as rheumatoid arthritis and inflammatory bowel diseases. Although research into olfactory stimulation has been observed on the ANS, it is still lacking in the exploration of odor concentration and odor-specific effects. This is particularly the case as research has not utilized specified tools, such as the olfactometer to provide precise odor delivery. Furthermore, no research has compared the results in separate sex cohorts to investigate the role of sex or the menstrual stage on the subsequent interactions. In this study, we investigated the olfactory stimulation effects of four natural odors (mushroom, lavender, jasmine, and rose) in three concentrations (low, moderate, and high) on the ANS. To observe activity from the ANS, we used an electrocardiogram (ECG) based heart rate variability (HRV) and eye-tracker technology (pupil diameter). We found for the first time in literature that there were acute dose- and duration-specific odor effects of odors on the ANS. We also found sex and menstrual cycle effects in this interaction. Furthermore, there were stark distinctions in sympathovagal activity dependent ANS activation (HRV) in comparison to the oculomotor nerve-parasympathetic/cervical sympathetic nerves dependent ANS responses (pupil diameter). Sympathovagal activity dependent HRV showed odor, sex, and menstrual-stage interactions in both divisions of the ANS while the pupil responses only indicated increased sympathetic activation. These results shed light on the use of odor-specific stimulation to modulate the ANS activity in the context of sex and the menstrual stage. Future studies should be performed using a chronic odor delivery design to investigate the long-term effects of odors on the ANS. Clinical trial registration Australian New Zealand Clinical Trials Registry, identifier [ACTRN12622000415707].